Dynamic characteristics analysis of disc-spring longitudinal shock absorber of ship shafting - Ji XIA (Zhongguo Jianchuan Yanjiu, 2021)
ObjectivesIn order to suppress the longitudinal vibration transfer of ship shafting, this paper put forward a design approach of applying disc-spring longitudinal shock absorber to the ship shafting, and carried out a study of dynamic characteristics before and after applying this type of longitudinal shock absorber. MethodsFirst, the static stiffness of shock absorber was studied by theoretical analysis and experimental test. Secondly, the influence of static load, excitation frequency, disc spring combination and other factors on the dynamic stiffness of shock absorber was investigated by experimental test. Finally, the optimized scheme of disc-spring shock absorber was applied to ship shafting to study the effect of vibration reduction. Results The results show that the selected four-piece dual disc-spring shock absorber has a low ratio of dynamic stiffness to static stiffness, and its dynamic stiffness is not sensitive to the variation of static load, system excitation frequency and other factors. The application of shock absorber has obvious effect on longitudinal vibration control of shafting. Conclusions The research results have reference value for the engineering application of ship shafting disc-spring longitudinal shock absorber.